Interface for operational management system in marshalling yards - Šohajek, Petr; Čáp, Jiří (University of Pardubice, 2018)
This paper considers existing procedures that are performed in marshalling yards with empiric measured times of duration of main operations. In the first part of the paper are mentioned sources which are used for performing of the operations with inbound and outbound trains that are analysed afterward. Following part describes circumstances of non-optimised decisions and the reasons for them. In last part of the paper is stated proposal of data interface which is necessary for improvement of data flow in marshalling yards and is a base for development of considered marshalling yard management system.
Keywords: marshalling yard; processes; interface; sources